Simultaneous solar photo-degradation of PVC-Fe-doped ZnO-nanocomposite flakes and Methylene Blue dye in water - Roy, Anirban; Chakrabarti, Sampa; Maitra, Saikat (Journal of Environmental Engineering and Landscape Management, 2022)
Simultaneous solar photocatalytic decolorization of Methlene Blue (MB) dye and degradation of polymer nanocomposite film in water has been attempted in the present work. The film immobilized iron (Fe)-doped zinc oxide (ZnO) nanoparticles (NPs) in polyvinyl chloride (PVC) matrix. This reduced the cost of separation of nanoparticles from treated water. Doped NPs were prepared sonochemically using zinc acetylacetonate (0.95 mmol) and ferric acetylacetonate (0.05 mmol) precursors in aqueous ethanol medium. XRD, UV-vis spectroscopy, FESEM and EDX were used for characterizing nanoparticles whereas the film was characterized by SEM. During the process, the film also reduced in weight. Degradation of both the dye and the polymer followed pseudo-first order kinetics. About 28% of the initial concentration of dye and about 5.04% of the initial weight of the PVC-film were decreased in the process after a run time of 3 h 45 minutes.